2022
DOI: 10.3390/molecules27061950
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Methyl Methanesulfonate and Ethyl Methylsulfonate in New Drug for the Treatment of Fatty Liver Using Derivatization Followed by High-Performance Liquid Chromatography with Ultraviolet Detection

Abstract: A new derivatization high-performance liquid chromatography method with ultraviolet detection was developed and validated for the quantitative analysis of methanesulfonate genotoxic impurities in an innovative drug for the treatment of non-alcoholic fatty liver disease. In this study, sodium dibenzyldithiocarbamate was used as a derivatization reagent for the first time to enhance the sensitivity of the analysis, and NaOH aqueous solution was chosen as a pH regulator to avoid the interference of the drug matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Preclinical studies have suggested that IMM, the bicyclic morpholine mesylate of bicyclol, has better pharmacological activities and pharmacokinetic properties than bicyclol in the aspects of liver protection and therefore holds great promise as a useful drug for treating NAFLD in the future. Moreover, as a methanesulfonate drug, the residues of methyl methanesulfonate and ethyl methylsulfonate were well below control limits [9]. IMM is currently in Phase I clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have suggested that IMM, the bicyclic morpholine mesylate of bicyclol, has better pharmacological activities and pharmacokinetic properties than bicyclol in the aspects of liver protection and therefore holds great promise as a useful drug for treating NAFLD in the future. Moreover, as a methanesulfonate drug, the residues of methyl methanesulfonate and ethyl methylsulfonate were well below control limits [9]. IMM is currently in Phase I clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a selective high-performance liquid chromatography (HPLC) method and a sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method have been developed and validated for quantitative analysis of impurities [18]. A novel derivatization HPLC method has also been developed for genotoxic impurities [19]. Reference materials (RMs) for active pharmaceutical ingredients (APIs) and their impurities at an accurate and reliable purity are essential for quality control studies.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these analysis methods were performed using a gas chromatography or liquid chromatography system, altered according to the characteristics of each impurity, alongside a mass spectrometry detector capable of detecting trace amounts of impurities. Other literature studies used detectors other than the mass spectrometry detector along with their respective chromatographic systems [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The analytical quality by design (QbD) approach can be a good tool for the development of an optimally robust analytical method for PGIs [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%